Paint & Painting (London : Tate Gallery, 1982)
Daumier, Honoré ; Wallis, Henry ; Gilman, Harold ; Turner, J.M.W. ; Constable, John ; Brown, Ford Madox ; Gauguin, Paul ; Degas, Edgar ; Ernst, Max ; Pollock, Jackson ; Blake, Peter ; etc.
Paint & Painting, The Tate Gallery, London, 9 June - 18 July 1982
boek